Dysregulated KRAS gene-signaling axis and abnormal chromatin remodeling drive therapeutic resistance in heterogeneous-sized circulating tumor cells in gastric cancer patients. (1st October 2021) - Chen, Yang; Li, Yanyan; Qi, Changsong; Zhang, Cheng; Liu, Dan; Deng, Youping; Fu, Yuanyuan; Khadka, Vedbar S.; Wang, Daisy Dandan; Tan, Shanyang; Liu, Shujun; Peng, Zhi; et al.
Abstract: The mechanism by which heterogeneous-sized circulating tumor cells (CTCs) in gastric cancer (GC) patients are resistant to the targeted therapy and/or chemotherapy remains unclear. This study investigated prognostic value and genomic variations of size-heterogenous CTCs, in an attempt to unravel the molecular mechanisms underlying the therapeutic resistance, which is relevant to poor prognosis in GC. Aneuploid CTCs, detected in 111 advanced GC patients, were categorized into small (≤white blood cell [WBC], 25.54%) and large (>WBC, 74.46%) cells. Pre-treatment patients possessing ≥3 baseline small CTCs with trisomy 8 (S CTCs tri ) or ≥6 large multiploid CTCs (L CTCs multi ) showed an inferior median progression-free survival. Moreover, the cut-off value of ≥6 L CTCs multi was also an effective prognosticator for poor median overall survival. Single cell-based DNA sequencing of 50 targeted CTCs indicated that S CTCs tri and L CTCs multi harbored distinct gene variations respectively. Mutations in the KRAS and Rap1 pathway were remarkably abundant in S CTCs tri, whereas several unique mutations in the MET/PI3K/AKT pathway and SMARCB1 gene were identified in L CTCs multi . Obtained results suggested that S CTCs tri and L CTCs multi exhibited different mechanisms to therapy resistance and correlated with patients' poor outcome. Highlights: ● CTCs in heterogeneous sizes correlated with the therapy resistance. ● Patients possessing S CTCs tri (≥3) or L CTCs multi (≥6) had an inferior PFS and OS. ● S CTCs tri and L CTCs multi contribute to therapeutic resistance via diverse mechanisms. ● Dysregulated KRAS signaling axis contributes to S CTCs tri - associated resistance. ● SMARCB1- mediated abnormal chromatin remodeling drives resistance in L CTCs multi .